Artistic Creativity Between Human and Generative Models: Conceptual Transformations in Contemporary Art (Al-Academy, 2026)
This study explores the transformation of artistic creativity in contemporary art, tracing its shift from a human centered practice based on intentionality and aesthetic perception to a generative model shaped through interaction with Artificial Intelligence. Traditionally understood as an act rooted in intuition and imagination, creativity is increasingly reconceptualized as a distributed process involving both human and algorithmic systems. Using a descriptive/analytical approach, the study analyzes changes in artistic practice and the emergence of new creative forms within digital contexts. The findings indicate a fundamental redefinition of key concepts, including originality, authorship, and aesthetic value. Accordingly, creativity is no longer viewed as the product of an autonomous individual, but as a co-creative process integrating human cognition with computational systems, repositioning the artist as a designer of generative processes and a curator of their outcomes.